Microbial Profile of Maize - Pigeon Pea Biscuit in Storage (Fountain Journal of Natural and Applied Sciences, 2013)
The production of biscuit from a blend of maize (Zea mays) and pigeon pea (Cajanus cajan) flour had earlier been reported in the literature. However, there is no information on the shelf stability of the biscuit. This study therefore investigated the microbial profile of the biscuit stored for 30 days atÂ Â  29 oC and 70 % relative humidity. The proximate and microbiological qualities of the biscuit were determined using standard methods. Biscuit had 5.19 % moisture, 1.90 % ash, 21.59 % fat, 0.62 % crude fibre, 15.83 % protein and 54.86 % carbohydrate. The microbial load of the biscuit was below the standard limit of National Food and Drug Administration and Control (NAFDAC) on the day of production but increased above the permissible level during storage. Staphylococcus, Enterobacter and Bacillus species were found in the biscuit during storage. The public health importance of these microorganisms was discussed.Keywords: biscuit, maize, pigeon pea, microorganisms